Can achievement compensate for low inclusiveness in multilingual work groups? A multilevel model. Issue 4 (21st February 2022) - Lauring, Jakob; Nygaard, Kenneth
Abstract: Individuals' involvement has been found to be vital to the functioning of diverse work groups. Work group involvement, however, is difficult to achieve in the increasingly internationalized environment that exists in knowledge intensive organizations. Based on developments in social identity theory and sports team psychology we set out to explore two types of group activities that can lead to involvement, namely relation-oriented activities that can lead to inclusiveness (being open to language diversity) and task-oriented activities that can lead to achievement orientation (bringing expertise to bear). Our main hypothesis is that the two types of activities can substitute each other so that group inclusiveness becomes less important for feeling involved if group achievement is high. Using a multilevel approach and responses from 1124 individuals in 29 multicultural technical work groups in private business organizations and universities, we confirm our theoretical assumptions. While extant research has focused on the effect of relation- and task-oriented activities in isolation, our study contributes to existing research by showing that the two can substitute each other in a work group.